Metallic contamination of vegetables: causes and approach of solutions through environmental education - ATIDEGLA CAPO, Séraphin Cocou (My University, 2018)
This study aims to evaluate the causes of metallic contamination of vegetables produced in Grand-Popo in Benin and to propose some approaches to solutions through environmental education. Specifically, the assessment involved metal contamination by poultry manure used extensively by growers for crop fertilization. Laboratory analyzes were conducted to identify four heavy metals (copper, lead, cadmium and iron) in vegetable and poultry manure samples. The average levels of lead in carrots, big nightshade and tomato are respectively 41, 6 and 38 times higher than Benin standards while those of cadmium are respectively 25, 6 and 40 times. These levels revealed a relation between human activities and the degrees of contamination. The effects of piles of filth are not excluded in this contamination, the consequences of which are the health risks for consumers and producers. To remedy this situation, it is necessary to take steps to identify all potential sources of contamination. Those sources must be especially, domestic and commercial activities, in order to abandon or control them. In addition, some environmental education leads are proposed to help mitigate the impact of non-agricultural activities in this metal contamination.
Keywords: market gardening; heavy metals; vegetables; health risks; Benin